From “Angels” to “Vice Smugglers”: the Criminalization of Sea Rescue NGOs in Italy - Cusumano, Eugenio (European journal on criminal policy and research, 2021)
Non-governmental organizations (NGOs) have played a crucial role in conducting Search and Rescue (SAR) operations off the Libyan coast, assisting almost 120,000 migrants between 2014 and 2019. Their activities, however, have been increasingly criticized. The accusation that NGOs facilitate irregular migration has escalated into investigations by Italian and Maltese courts and various policy initiatives restricting non-governmental ships and their access to European ports. Although all NGOs investigated to date have been acquitted, the combination of criminal investigations and policy restrictions that has taken place in Italy since 2017 has severely hindered non-governmental SAR operations. Given the humanitarian repercussions of reducing NGOs’ presence at sea, the merits and shortcomings of the arguments underlying the criminalization of non-governmental maritime rescue warrant in-depth research. To that end, this article fulfils two interrelated tasks. First, it provides a genealogy of the accusation against NGOs and the ensuing combination of legal criminalization, policy restrictions, and social stigmatization in restraining their activities. Second, it uses quantitative data to show that empirically verifiable accusations like the claim that NGOs serve as a pull factor of migration, thereby causing more people to day at sea, are not supported by available evidence. By doing so, our study sheds new light onto the criminalization of humanitarianism and its implications.